Method for improving sphericity degree of glass beads in microgravity state
By simulating the microgravity environment in the tower dropping device, the problem of low spherical morphology of existing glass microbeads is solved, and higher spherical morphology and better mechanical properties are achieved.
Patent Information
- Application Number
- CN202411545165.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-01
Smart Images

Figure CN119461797A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of glass microbead preparation, and in particular to a method for improving the sphericity of glass microbeads under microgravity conditions. Background Art
[0002] Glass microspheres are a widely used inorganic filler material. Glass microspheres are processed from borosilicate and have a particle size of 1-250μm. Glass microspheres have the same chemical composition as glass fibers, and also have the advantages of low thermal conductivity and good chemical stability. In addition, due to their spherical appearance, glass microspheres have very good fluidity and dispersibility. In practical applications, glass microspheres with high sphericity are more popular with matching materials for the following reasons: (1) Improve the uniformity and stability of materials Glass microspheres with high sphericity are arranged more closely and orderly in the material, which helps to improve the uniformity and stability of the material. In coatings, spherical microspheres can provide a smoother surface effect, reduce the generation of bubbles and cracks, and thus improve the durability and aesthetics of the coating.
[0003] (2) Impact on mechanical performance Sphericity also has a significant effect on the mechanical properties of glass microspheres. Spherical microspheres are better able to withstand pressure when subjected to force because their shape makes the stress distribution more uniform. This means that microspheres with high sphericity can provide higher compressive strength and bending strength under the same volume.
[0004] (3) Affecting thermal conductivity The sphericity of glass beads also affects their thermal conductivity. Spherical beads have a relatively small surface area, which helps reduce the transfer of heat, so in applications where thermal insulation is required, beads with high sphericity can provide better thermal insulation.
[0005] (4) Influence on rheological properties In liquid or semi-solid materials, the rheological properties of spherical microspheres are also affected by the sphericity. Microspheres with high sphericity move more smoothly in the fluid, which helps to improve the fluidity and processability of the material, while also improving the surface superficiality and warping problems of the material, and also has a good effect on improving the wear resistance of the parts. In summary, sphericity has many effects on the application of glass microspheres, including improving the uniformity and stability of the material, improving mechanical properties, affecting thermal conductivity, and changing rheological properties. These factors must be taken into account when designing and using glass microspheres to ensure that the material can meet the requirements of specific applications.
[0006] In the actual production process of glass microspheres, the production equipment and process directly determine the degree of microsphere sphericity. For example, the melting environment, atmosphere mismatch, or uneven cooling rate may cause microsphere shape distortion and reduce sphericity. Figure 1 , Figure 2 As shown, Figure 1 It is a solid glass microsphere made by conventional method, and is measured by sphericity instrument Figure 1 The sphericity shown is 85%-88%, Figure 2 yes Figure 1 Polarized microscope photo of solid glass beads. Figure 2 You can see more intuitively Figure 1 The sphericity of solid glass beads is shown. Summary of the invention
[0007] The present invention aims to solve the problem that the existing glass microspheres have low sphericity and cannot achieve the ideal effect only through subsequent screening. A method for preparing glass microspheres is provided. The idea of the present invention is to prepare glass microspheres by strictly controlling the melting environment so that the glass microspheres can have a higher sphericity under the condition of the same particle size. At the same time, the preparation method of the ultra-high sphericity glass microspheres is also relatively simple.
[0008] It adopts the following technical solutions: A method for improving the sphericity of glass microspheres under microgravity: It uses a drop tower device, and the release system in the drop tower device releases the microgravity sintering furnace in the tower to free fall, thereby realizing the microgravity environment of the microgravity sintering furnace; The method for improving the sphericity of glass microspheres under microgravity comprises the following steps: S1, pretreatment stage: clean the surface of glass bead powder to remove impurities that may affect sintering quality; S2, the vacuum stage: the drop tower device is vacuumed to 30%-60% vacuum degree and maintained stable, the microgravity sintering furnace is vacuumed and the internal waste gas is discharged, so that the internal pressure range of the microgravity sintering furnace is consistent with the internal pressure range of the drop tower device; S3, heating stage: gradually raising the temperature in the microgravity sintering furnace to the sintering temperature of the glass microbead powder; S4, feeding stage: the microgravity sintering furnace forms a microgravity environment by free fall. In the microgravity environment, the glass microbead powder is sprayed into the microgravity sintering furnace by pressurizing the air through a compression pump; S5, sintering and molding stage: maintaining a constant sintering temperature of the microgravity sintering furnace in a microgravity environment to sinter the glass microbead powder; after the sintering of the glass microbead powder is completed, lowering the temperature in the microgravity sintering furnace to below the sintering temperature to form ultra-high sphericity glass microbeads; S6, collection stage: After the free fall of the microgravity sintering furnace ends, the microgravity sintering furnace is naturally cooled, and the cooled ultra-high sphericity glass microbeads are collected.
[0009] Furthermore, the sintering temperature is 1300°C-1500°C.
[0010] Furthermore, in step S4, the delivery amount of the glass bead powder is 0.2-0.4 kg of glass bead powder per kg of gas.
[0011] Furthermore, the glass microbead powder is solid or hollow.
[0012] Furthermore, the drop tower device also includes a tower body, a vacuum system for evacuating the tower body, and a deceleration recovery system for recovering and decelerating the microgravity sintering furnace to a stop when the free fall of the furnace ends, as well as a control system for accurately controlling and monitoring the entire process and a measurement system for measuring and recording various physical parameters in the entire process; the release system is used to freely release the microgravity sintering furnace from a high position in the tower body.
[0013] Furthermore, the drop tower device also includes auxiliary facilities for experimental environment control, data processing and analysis.
[0014] Compared with the prior art, the present invention has the following beneficial effects: The method for preparing glass microbeads into balls by using microgravity can effectively reduce the influence of gravity on the sphericity of the glass microbeads during the ball-forming process, and greatly improve the sphericity of the glass microbeads.
[0015] Specifically: The reason why glass beads can form a nearly circular shape when burning is mainly related to the physical properties of its material and the thermodynamic conditions during the heating process. Glass has surface tension in the molten state, which is an intermolecular attraction that makes liquid glass tend to form the shape with the smallest area, that is, a sphere. During the combustion process, the temperature inside the glass beads rises, causing the material to expand. Since the radius of curvature of the sphere is the same in all directions, this uniform expansion helps to maintain its spherical shape. At the same time, during the heating process, the gas around the glass beads will expand due to the influence of heat, forming a dynamic fluid environment, which can promote the beads to maintain a spherical shape because the fluid resistance will resist irregular changes in shape. In the conventional combustion heating process, the flame shape is related to the air convection under the influence of gravity. The hot gas in the flame will rise due to its low density, while the surrounding cold air will sink due to its high density, forming convection. This convection will cause the flame to change in shape, and the flame will rise upward to form a cone or funnel shape. This conical or funnel-shaped flame combined with gravity conditions will cause the thermal stress of the glass microspheres to be concentrated in one direction during the ball-forming process, resulting in deformation and reducing the sphericity of the overall glass solid microspheres.
[0016] Although many conventional combustion and heating processes are not obviously affected by gravity, for some high-demand glass microspheres, the theory that ignores the gravity effect often cannot give a satisfactory explanation for the degree of sphericity. The magnitude of the buoyancy effect in the glass microsphere combustion molding process can be estimated by two dimensionless parameters, namely, the Grashof number Gr = (Δρ / ρ)gL3 / ν2, which represents the ratio of buoyancy to viscosity, and the Richardson number Ri = (Δρ / ρ)gL / U2, which represents the ratio of buoyancy to inertia, where Δρ and ρ are density change and density, g is the gravitational acceleration, L is the characteristic size, ν is the kinematic viscosity coefficient, and U is the characteristic velocity. It can be seen that three methods can be used to reduce the influence of buoyancy: reduce the characteristic size L; reduce the density difference and increase the kinematic viscosity coefficient; reduce the gravitational acceleration g.
[0017] Among them, the first method is restricted by the minimum size limit and the observation method, so it is difficult to obtain ideal results; the second method will affect the chemical reaction; the third method does not have these defects. Combustion under microgravity conditions has the following characteristics: natural convection is almost eliminated, and static and low-speed flow combustion can be studied; secondary forces and phenomena such as electrostatic force, thermophoresis, thermocapillary force and diffusion that are masked by buoyancy and its induced effects can be manifested; gravity sedimentation is almost eliminated, and stable, freely suspended droplets, particles, and dust combustion can be studied; the elimination of buoyancy can increase the time and length scale of combustion. Therefore, according to the above basic theory, the method of preparing glass microspheres into balls using microgravity in a vacuum environment can effectively reduce the influence of gravity on the sphericity of glass microspheres during the balling process, and greatly improve the sphericity of glass microspheres. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 This is an electron microscope image of glass microbeads with low sphericity using conventional methods in the prior art; Figure 2 It is a polarization diagram of glass microbeads with low sphericity under conventional methods in the prior art; Figure 3 is a schematic structural diagram of a drop tower device in an embodiment of the present invention; Figure 4 This is an electron microscope image of glass microbeads with high sphericity using the method of the present invention; Figure 5 This is a polarization image of glass microbeads with high sphericity using the method of the present invention.
[0019] Explanation of reference numerals: 100, drop tower device; 110, tower body; 120, release system; 130, vacuum system; 140, deceleration recovery system; 150, control system; 160, recording and measuring system; 200, microgravity sintering furnace. DETAILED DESCRIPTION
[0020] To make the present invention more clear, a method for improving the sphericity of glass microspheres under a microgravity state of the present invention is further described below in conjunction with the accompanying drawings. The specific embodiments described here are only used to explain the present invention and are not used to limit the present invention.
[0021] A method for improving the sphericity of glass microbeads under microgravity conditions, which uses a drop tower device 100 to allow a microgravity sintering furnace 200 located in the drop tower device 100 to perform free fall, and the microgravity environment of the microgravity sintering furnace 200 is achieved by the drop tower method. The drop tower method is a technology that simulates a microgravity environment by free fall motion. In this method, an experimental device or sample is placed in a closed experimental device, and the experimental device is then released from a tall tower with a certain vacuum degree to perform free fall. When the experimental device falls freely in the tower, due to the lack of external force, all objects inside the device will experience the same acceleration, that is, the acceleration of gravity. During the falling process, these objects are stationary relative to each other, and the objects inside the experimental device will not feel gravity relative to each other, thereby simulating a microgravity or vacuum state.
[0022] In conjunction with the present application, the drop tower method requires the use of a drop tower device 100, specifically as follows Figure 3 As shown, the drop tower device 100 includes a tall tower body 110, and a release system 120 is provided on the top of the tower body 110. The release system 120 is used to freely release the microgravity sintering furnace 200 from the top of the tower body 110. A vacuum system 130 is arranged in the tower body 110. The vacuum system 130 is used to exhaust air in the tower body 110 to form a certain vacuum degree. A deceleration recovery system 140 is arranged at the lower part of the tower body 110. The deceleration recovery system 140 can recover the microgravity sintering furnace 200 at the end of free fall and buffer and decelerate it to stop. The drop tower device 100 also includes a control system 150 for accurately controlling and monitoring the entire process and a measurement system 160 for measuring and recording various physical parameters in the entire process, as well as auxiliary facilities for experimental environment control, data processing and analysis.
[0023] The microgravity sintering furnace 200 has a basically the same structure as a conventional sintering furnace, and also has structures such as a heating unit, a vacuum unit, a gas inlet and outlet unit, and a feeding unit, and has conventional functions such as gas extraction, heating, heat supply, and sintering. The difference is that the microgravity sintering furnace 200 can be in free fall in the tower body 110. During the free fall of the microgravity sintering furnace 200, the delivery path of the gas, powder, and energy supply can be realized by a sufficiently long flexible delivery pipe, and the free fall of the microgravity sintering furnace 200 is not affected at the same time. The relevant data transmission can be realized by wired or wireless means. Of course, other methods can also be used to deliver the gas, powder, and energy of the microgravity sintering furnace 200 without affecting the free fall.
[0024] The method for improving the sphericity of glass microspheres under microgravity comprises the following steps: S1, pretreatment stage: clean the surface of glass bead powder to remove impurities that may affect the sintering quality.
[0025] S2. Vacuuming stage: The inside of the tower body 110 of the drop tower device is evacuated to 30%-60% vacuum degree and maintained stable through the vacuum system 130; the microgravity sintering furnace 200 is evacuated and its internal exhaust gas is discharged to make the internal air pressure range of the microgravity sintering furnace consistent with the internal air pressure range of the drop tower device; this step is crucial for eliminating the influence of other gases in the furnace and realizing microgravity heating.
[0026] S3, heating stage: gradually raising the temperature in the microgravity sintering furnace 200 until the sintering temperature of the glass microbead powder is reached. In this embodiment, the sintering temperature is 1300°C-1500°C.
[0027] S4, feeding stage: using the drop tower method, the microgravity sintering furnace 200 is released to free fall through the release system 120, so that the microgravity sintering furnace 200 is in a microgravity environment. In this environment, the glass microbead powder is sprayed into the microgravity sintering furnace 200 by pressurizing the air through a compression pump, that is, the feeding is performed during the free fall of the microgravity sintering furnace 200. Among them, each kilogram of gas contains about 0.2-0.4 kilograms of glass microbead powder.
[0028] S5, sintering and molding stage: maintain a constant sintering temperature of the microgravity sintering furnace in a microgravity environment to sinter the glass microbead powder. After the sintering of the glass microbead powder is completed, reduce the temperature in the microgravity sintering furnace 200 to below the sintering temperature. For example, the heat source switch of the microgravity sintering furnace 200 can be turned off. The temperature in the microgravity sintering furnace is lower than the sintering temperature, and the ultra-high sphericity glass microbeads are formed, and the sphericity no longer changes. This stage lasts about 2-3s, which can ensure that the glass microbeads are fully melted and recrystallized. This stage is the most critical part of the entire preparation process, which determines the microstructure and final performance of the microbeads.
[0029] After the heat source in the microgravity sintering furnace is turned off at the end of the sintering of the glass microsphere powder, and before the free fall of the drop tower ends, the temperature in the microgravity sintering furnace is lower than the sintering temperature, and the ultra-high sphericity glass microspheres are formed, and the sphericity no longer changes. S6. Collection stage: When the free fall of the microgravity sintering furnace 200 ends, it can be recovered and buffered and decelerated to a stop through the deceleration recovery system 140. At the same time, the sintering of the glass bead powder is completed. Then the microgravity sintering furnace 200 is naturally cooled, usually to 30°C-60°C for easy collection, and then the cooled ultra-high sphericity glass beads are collected through a collection device.
[0030] The following experimental tests were performed using this method: Hollow glass microsphere series: Implementation Group 1 The M series hollow glass microsphere raw powder was selected. The hollow glass microspheres obtained under normal sintering conditions have a sphericity of 85%-87%. The compressive strength was 6,000Psi (20% breakage rate) tested by a hollow glass microsphere (gas) pressure tester.
[0031] By adopting the method of this application, the vacuum degree of the drop tower device is maintained at 30%, and the free fall time of the microgravity sintering furnace 200 is about 5~6s. 0.5-1kg of hollow glass microsphere powder can be sintered within a limited time. The sintered hollow glass microsphere powder is collected, gravity floated and dried, and the sphericity is increased to 90%. After testing by the hollow glass microsphere (gas) pressure tester, the compressive strength can be increased from the initial 6,000Psi (20% crushing rate) to 8,000Psi (20% crushing rate).
[0032] Implementation Group 2 The M series hollow glass microsphere raw powder was selected. The hollow glass microspheres obtained under normal sintering conditions have a sphericity of 85%-87%. The compressive strength was 6,000Psi (20% breakage rate) tested by a hollow glass microsphere (gas) pressure tester.
[0033] By adopting the method of this application, the vacuum degree of the drop tower device is maintained at 50%, and the free fall time of the microgravity sintering furnace 200 is about 5~6s. 0.5-1kg of hollow glass microsphere powder can be sintered within a limited time. The sintered hollow glass microsphere powder is collected, gravity floated and dried, and the sphericity is increased to 92%. After testing by the hollow glass microsphere (gas) pressure tester, the compressive strength can be increased from the initial 6,000Psi (20% crushing rate) to 9,000Psi (20% crushing rate).
[0034] Implementation Group 3 The M series hollow glass microsphere raw powder was selected. The hollow glass microspheres obtained under normal sintering conditions have a sphericity of 85%-87%. The compressive strength was 6,000Psi (20% breakage rate) tested by a hollow glass microsphere (gas) pressure tester.
[0035] By adopting the method of this application, the vacuum degree of the drop tower device is maintained at 60%, and the free fall time of the microgravity sintering furnace 200 is about 5~6s. 0.5-1kg of hollow glass microsphere powder can be sintered within a limited time. The sintered hollow glass microsphere powder is collected, gravity floated and dried, and the sphericity is increased to 95%. After testing by the hollow glass microsphere (gas) pressure tester, the compressive strength can be increased from the initial 6,000Psi (20% crushing rate) to 11,000Psi (20% crushing rate).
[0036] Solid glass microsphere series: Implementation Group 4 The solid glass microsphere powder is selected and sintered in a traditional sintering furnace to form solid glass microspheres with a sphericity of 85%-88%. Figure 1 , Figure 2 shown.
[0037] By adopting the method of this application, the vacuum degree of the drop tower device is maintained at 30%, and the free fall time of the microgravity sintering furnace 200 is about 5~6s. 1-2kg of solid glass microbead powder can be sintered within a limited time. After testing, the sphericity can be increased to 92%. Figure 4 , Figure 5 shown.
[0038] Implementation Group 5 The solid glass microsphere powder is selected and sintered in a traditional sintering furnace to form solid glass microspheres with a sphericity of 85%-88%. Figure 1 , Figure 2 shown.
[0039] By adopting the method of the present application, the vacuum degree of the drop tower device is maintained at 50%, and the free fall time of the microgravity sintering furnace 200 is about 5-6s. 1-2kg of solid glass microbead raw powder can be sintered within a limited time. After testing, the sphericity can be increased to 95%.
[0040] Implementation Group 6 The solid glass microsphere powder is selected and sintered in a traditional sintering furnace to form solid glass microspheres with a sphericity of 85%-88%. Figure 1 , Figure 2 shown.
[0041] By adopting the method of the present application, the vacuum degree of the drop tower device is maintained at 60%, and the free fall time of the microgravity sintering furnace 200 is about 5-6s. 1-2kg of solid glass microbead raw powder can be sintered within a limited time. After testing, the sphericity can be increased to 97%.
[0042] It can be seen from the above test group that the use of this application method can effectively reduce the influence of gravity on the sphericity of glass microspheres during the ball-forming process, greatly improve the sphericity of glass microspheres, and the method is also relatively simple.
[0043] The above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. However, these obvious changes or modifications derived from the essential spirit of the present invention still fall within the scope of protection of the present invention.
Claims
1. A method for improving the sphericity of glass microspheres under microgravity, characterized in that: It uses a drop tower device (100), and a release system (120) in the drop tower device (100) releases the microgravity sintering furnace (200) in the tower to free fall, thereby realizing a microgravity environment of the microgravity sintering furnace (200); The method for improving the sphericity of glass microspheres under microgravity comprises the following steps: S1, pretreatment stage: clean the surface of glass bead powder to remove impurities that may affect sintering quality; S2, the exhaust phase: the drop tower device (100) is evacuated to a vacuum degree of 30%-60% and maintained stable, and the microgravity sintering furnace (200) is evacuated and the waste gas inside is discharged, so that the internal pressure range of the microgravity sintering furnace (200) is consistent with the internal pressure range of the drop tower device (100); S3, heating stage: gradually raising the temperature in the microgravity sintering furnace (200) to the sintering temperature of the glass microbead powder; S4, feeding stage: the microgravity sintering furnace (200) forms a microgravity environment by free fall, and in the microgravity environment, the glass microbead powder is sprayed into the microgravity sintering furnace (200) by applying pressure to the air through a compression pump; S5, sintering and molding stage: maintaining a constant sintering temperature of the microgravity sintering furnace (200) in a microgravity environment to sinter the glass microbead powder; after the sintering of the glass microbead powder is completed, lowering the temperature in the microgravity sintering furnace to below the sintering temperature to form ultra-high sphericity glass microbeads; S6, collection stage: after the free fall movement of the microgravity sintering furnace (200) ends, the microgravity sintering furnace is naturally cooled, and the cooled ultra-high sphericity glass microbeads are collected.
2. The method for improving the sphericity of glass microspheres under microgravity according to claim 1, characterized in that: The sintering temperature is 1300°C-1500°C.
3. The method for improving the sphericity of glass microspheres under microgravity according to claim 1, characterized in that: In step S4, the delivery amount of glass bead powder is 0.2-0.4 kg of glass bead powder per kg of gas.
4. The method for improving the sphericity of glass microspheres under microgravity according to claim 1, characterized in that: The glass microbead powder is solid or hollow.
5. The method for improving the sphericity of glass microspheres under microgravity according to any one of claims 1 to 4, characterized in that: The drop tower device (100) further comprises a tower body (110), a vacuum system (130) for evacuating the tower body (110), a deceleration recovery system (140) for recovering the microgravity sintering furnace (200) and decelerating it to a stop when the free fall of the microgravity sintering furnace (200) ends, a control system (150) for accurately controlling and monitoring the entire process, and a measurement system (160) for measuring and recording various physical parameters in the entire process; the release system (120) is used to freely release the microgravity sintering furnace (200) from a high position of the tower body (110).
6. The method for improving the sphericity of glass microspheres under microgravity according to claim 5, characterized in that: The drop tower device (100) also includes auxiliary facilities for experimental environment control, data processing and analysis.
Citation Information
Patent Citations
Method and device for balling hollow glass microballoons through oxygen-enriched combustion
CN101638291A
Material smelting and welding experimental apparatus under ground microgravity and methods for smelting and welding material under microgravity based on device
CN103323568A
Method for foaming and nodulizing hollow glass microspheres under high negative pressure by utilizing flame
CN104310761A
Glass bead forming process based on glass arrangement angle distribution heating
CN117486468A
Method and device for producing glass bead
JP2005029425A
Cited By
Method for improving sphericity of glass microsphere under microgravity condition
WO2026091677A1